2014
DOI: 10.1063/1.4896614
|View full text |Cite
|
Sign up to set email alerts
|

An (e, 2e + ion) study of low-energy electron-impact ionization and fragmentation of tetrahydrofuran with high mass and energy resolutions

Abstract: We study the low-energy (E0 = 26 eV) electron-impact induced ionization and fragmentation of tetrahydrofuran using a reaction microscope. All three final-state charged particles, i.e., two outgoing electrons and one fragment ion, are detected in triple coincidence such that the momentum vectors and, consequently, the kinetic energies for charged reaction products are determined. The ionic fragments are clearly identified in the experiment with a mass resolution of 1 amu. The fragmentation pathways of tetrahydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 35 publications
(74 reference statements)
1
46
0
Order By: Relevance
“…The basic principles of a general reaction microscope have been described by Ullrich et al [60]. Details of the experimental method are described in one of our earlier studies [56]. Here, we provide a short description on the experimental setup used for the present set of measurements.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The basic principles of a general reaction microscope have been described by Ullrich et al [60]. Details of the experimental method are described in one of our earlier studies [56]. Here, we provide a short description on the experimental setup used for the present set of measurements.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…To perform these experiments, we used an advanced reaction microscope which is built especially for electronimpact ionization studies [56,60]. The basic principles of a general reaction microscope have been described by Ullrich et al [60].…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…• C. The extended mass spectrum of Ren's publication [30] indeed shows a 5% contribution around 144 amu, but in our mass spectra we could not find any dimer. Note, that we are comparing mass spectra of low-energy electron-impact and high-energy proton-impact, so that not all differences are due to cluster formation.…”
Section: Tetrahydrofuranmentioning
confidence: 65%
“…In an electron impact experiment with variable delays between ionization and ion extraction we previously found that the dissociation channels can be distinguished by the kinetic energy release (unpublished, paper in preparation). Kinetic energies of different mass peaks have been discussed by Ren [30] but competing dissociation channels hidden in one mass peak are not resolved in their work. From calculation of the standard enthalpy of formation, Collin attributes mass 42 to C 3 H + 6 [24], after Gallegos found C 2 H 2 O + to be more likely [23].…”
Section: Tetrahydrofuranmentioning
confidence: 99%